Implementación de un sistema de gestión para el seguimiento de proyectos de titulación de la Universidad Técnica de Cotopaxi Extensión La Maná, 2017" - Barrera Hurtado, Kenny Xavier (2017)
The present research project had as general objective the implementation of a management system for the monitoring of projects of titling of the students of the Technical University of Cotopaxi - La Maná. Its approach emerged as an alternative of improvement, facing the problem of scarce level of automation of the processes in relation to the degree in that institution. The types of research that allowed each of the objectives to be fulfilled were of an exploratory type whose use highlighted the fundamental aspects of the problem of the lack of a digital system that contributes to the obtaining of information about investigative work carried out. The implemented system was developed using the SCRUM methodology, whose selection is due to its ability to work with highly productive equipment, the creation of the database and graphical interface using MySQL, was exposed to tests of white box and black box, detecting As well as several errors. The main beneficiaries will be the teachers and students because they will be able to count on up-to-date information on titling projects that have already been carried out, and on the processes, thus contributing to the optimization of time with respect to the approval process.